A low-cost amperometric sensor for the combined state-of-charge, capacity, and state-of-health monitoring of redox flow battery electrolytes. (May 2022) - Stolze, Christian; Rohland, Philip; Zub, Karina; Nolte, Oliver; Hager, Martin D.; Schubert, Ulrich S.
Highlights: Simultaneous state-of-charge, capacity, and state-of-health measurement on half-cell level. Temperature-independent, concentration-independent, calibration-free, and cost-efficient. Reduced absolute state-of-charge measurement error to <0.5% over complete range. Electrolyte capacity and state-of-health are monitored with relative errors of <2% Cost-efficient microcontroller-based measurement unit is presented and characterized. Abstract: We recently introduced an amperometric, temperature-independent, and calibration-free method for the measurement of the state-of-charge (SOC) of redox flow battery (RFB) electrolytes. In the study at hand, the measurement accuracy of the method is re-evaluated and significantly improved. The absolute root-mean-square deviation (RMSD) is reduced from ∼ 5% to below 0.5% over the complete SOC range. Based on this enhanced measurement accuracy, a new approach for the online co-estimation of an electrolyte's capacity and its state-of-health (SOH) is proposed and experimentally evaluated. In an operating RFB, relative RMSDs of 0.7 and 1.4% are obtained for the capacities of the catholyte and the anolyte, respectively. Utilizing this capacity measurement, SOH values with absolute RMSDs between 0.6 and 2.1% can be achieved. Furthermore, a low-cost microcontroller-based measurement unit (MMU) prototype was constructed and characterized. Based on the component prices and possible cost optimizations, total material costs of below 40 EUR (49) for two MMUs are calculated. In addition, a preliminary investigation of a low-cost bipolar, backfilled microelectrode (BBME) for material costs of below 2 EUR (2) is presented, its working principle demonstrated, and pathways for mitigating its stability issues are discussed. The methodological enhancements proposed in this study result in unprecedented measurement accuracies for the simultaneous SOC and SOH monitoring of both electrolytes in an operating RFB. The improved amperometric method stands out for its wide applicability, viable implementation costs, temperature as well as concentration independence, and excellent accuracy level. It, thus, has the potential to facilitate the RFB electrolyte development, improve the operational safety of RFBs, and optimize their operational performance.